A Case of Obstructive Sleep Apnea and Assessments of Fitness for Work - Hong, Sukwoo (BioMed Central, 2014)
BACKGROUND: Obstructive sleep apnea is a common sleep disorder that can cause excessive daytime sleepiness and impairment of cognition. These symptoms may lead to the occurrence of occupational accidents in workers with obstructive sleep apnea. CASE PRESENTATION: A 36-year-old man who worked as a dimensional control surveyor caused a vehicle accident while he was driving at the work site. Although he experienced loss of consciousness at the time of the accident, he had no other symptoms. His brain computed tomography and laboratory test did not show any specific findings. Medical tests were conducted to evaluate his fitness for work. Decreased sleep latency was observed on the electroencephalography image, which is suggestive of a sleep disorder. He frequently experienced daytime sleepiness and his Epworth sleepiness score was 13. The polysomnography showed a markedly increased apnea-hypopnea index of 84.3, which led to a diagnosis of severe obstructive sleep apnea. The patient was advised to return to work only when his obstructive sleep apnea improved through proper treatment. CONCLUSION: Proper screening for obstructive sleep apnea among workers is important for preventing workplace accidents caused by this disorder, but screening guidelines have not yet been established in Korea. An effort toward preparing practical guidelines for obstructive sleep apnea is needed.